INOVASI PEMBELAJARAN BLENDED LEARNING DENGAN METODE PROJECT BASED LEARNING TERHADAP MOTIVASI, MINAT DAN HASIL BELAJAR SISWA DI MASA PANDEMI COVID-19 - suryani, lilis; Susilawati, Tri; Harjito (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
This study aims to: (1) find out how big the relationship between the application of blended learning innovations with project based learning methods on student learning motivation (2) find out how big the relationship between the application of blended learning innovations with project based learning methods on student learning outcomes (3) Knowing how big the relationship between the application of blended learning innovation and project based learning method on students' interest in learning (4) Knowing how big the relationship between the application of blended learning innovation and project based learning method on students' interest and motivation. This research is a quantitative research with a quasi-experimental type of research. The results showed that: (1) there was no significant relationship between the learning outcomes of blended learning and project based learning methods on students' learning motivation; (2) there is no significant relationship between the learning outcomes of blended learning and project based learning methods on interest in learning; (3) there is no relationship between blended learning learning outcomes and project based learning methods on interest and motivation; (4) There is a significant effect between blended learning and project based learning methods on student learning outcomes.